Community-based research: Engaging universities in technology-related knowledge exchanges. Issue 3 (September 2018) - Chan, Yolande E.; Farrington, Conor J.T.
Abstract: Many universities are disengaged from their local regions. While universities are hotbeds of knowledge with the potential to generate new and disruptive technologies, their development strategies and public relations engagements rarely emphasize the potential of universities to act as local and regional economic engines. Similarly, information systems (IS) and other scholars generally aim to make international, not local impacts. Local contributions are often viewed as distractions from more visible and highly rewarded roles in the global scholarly community, such as publishing in international journals. This Global Challenge article argues that universities' local ecosystems are appropriate targets for IS scholarly activity, particularly when this is undertaken in the form of community-based research (CBR). Following conceptual discussions of 'community' and key elements of CBR, we draw on the authors' personal research experiences to evaluate the potential contributions of IS scholars in terms of CBR projects focused on technology-related knowledge exchanges. After outlining implications and potential future directions for IS researchers, we close by presenting a call to IS scholars to intensify their local ecosystem research collaborations in technology-related knowledge exchange contexts, in order to increase the relevance and local impact of their research. Highlights: While IS scholars and universities more widely are frequently disengaged from their local communities, significant research and impact opportunities arise when scholars participate in community-based research (CBR) IS scholars have particular strengths to offer in terms of CBR projects focused on technology-related knowledge exchange, engaging IS expertise in economic, social, and relational contexts Challenges as well as opportunities arise in CBR projects, but these can be managed (if not eliminated) through the close involvement of multiple community stakeholders